1976
DOI: 10.1149/1.2133017
|View full text |Cite
|
Sign up to set email alerts
|

The Electrical Properties of Protective Polymer Coatings as Related to Corrosion of the Substrate

Abstract: The effective electrical permittivity of polymer‐coated steel was measured between 200 Hz and 100 kHz as a function of time of exposure to 0.52MnormalNaCl . The real and imaginary parts of the permittivity increased over the entire frequency range as a consequence of electrolyte penetration. The development of a −1 slope on the log loss vs. log frequency curve suggested localized penetration of the dielectric coating by a conducting phase. This behavior correlated with the onset of visible localized corrosion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0

Year Published

1985
1985
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(52 citation statements)
references
References 10 publications
3
49
0
Order By: Relevance
“…Further studies [14][15][16] revealed that under-film corrosion initially occurs at D type areas and then spreads from the interface as initiated by cathodic disbonding. It has been also shown that the mechanism of ionic conduction and local inhomogeneity of the polymer film plays a major role in the failure mode of protective coatings [17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Further studies [14][15][16] revealed that under-film corrosion initially occurs at D type areas and then spreads from the interface as initiated by cathodic disbonding. It has been also shown that the mechanism of ionic conduction and local inhomogeneity of the polymer film plays a major role in the failure mode of protective coatings [17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies [22,23] have found that 1% lactic acid on chromium-passivated tin plates and protected by organic compounds can be attacked by corrosion currents due to the presence of pores We must notice the appearance of new bands related to the yellow spots in Figure 1 and with the spectra observed in Sample 2; these bands are mainly those seen at 960 cm´1, 1260 cm´1, 1300 cm´1, 1440 cm´1 and 1657 cm´1. These resonance waves are not attributed to vibration modes in the PET coating or to the rutile load that gives the white color to the polymer.…”
Section: Discussionmentioning
confidence: 68%
“…Other studies [22,23] have found that 1% lactic acid on chromium-passivated tin plates and protected by organic compounds can be attacked by corrosion currents due to the presence of pores and interfacial defects that allow degradation and loss of functionality at pH 2-3. The postmortem salmon produces lactic acid and may be one of the sources of organic acid that may act on the container-food system.…”
Section: Discussionmentioning
confidence: 99%
“…This interpretation of behavior organic coatings on steel and aluminum alloys and effect of corrosion agent is found by numerous authors. [10][11][12][13][14] An equivalent electrical circuit model for the behavior of polymer-coated metal in corrosive environments has been used (Figure 1), where R Ω is the resistance of the electrolyte, R p is the coating pore resistance due to electrolyte penetration, C c is the coating capacitance, R ct is the charge-transfer resistance, Z w is the Warburg impedance. By fitting the experimental data, from the impedance plots in the complex plane, 15 the pore resistance, R p , coating capacitance, C c , charge-transfer resistance, R ct and double-layer capacitance, C d were determined and plotted as function of time in Figures 2, 3, 4 and 5, respectively.…”
Section: Resultsmentioning
confidence: 99%